Cheese bread enriched with biofortified cowpea flour - Cavalcante,Rodrigo Barbosa Monteiro (2016)
ABSTRACT The development and enrichment of food are of great importance not only for the industry but also to improve the population's nutrition, where you can create new products or optimize existing ones. The consumption of fortified products in the diet is an option for the control of deficiency diseases. This study aimed to develop enriched cheese bread with whole biofortified cowpea flour and evaluate their acceptance and chemical composition. Two formulations, F1 and F2, were prepared containing 5.6 and 8% of cowpea flour as a substitute for starch, respectively. To check acceptance, three sensory tests were used (Hedonic Scale, Purchase Intent, and Paired Comparison), F1 being sensory viable according to assessors, being chemically analyzed. Minerals were determined by atomic emission spectrometry with inductively coupled plasma source. The moisture was determined by drying at 105 °C, ash by calcination in muffle at 550 °C, proteins by the macro-Kjeldahl method, and lipids by hot extraction in a Soxhlet extractor. Carbohydrates were obtained by difference and the calories were calculated. The addition of cowpea increased the amounts of copper, iron, phosphorus, magnesium, manganese, and zinc, as well as protein and carbohydrate values. On the other hand, there was a reduction of the moisture concerning lipids and the total caloric value compared to the standard formulation. It was concluded , therefore, that the cowpea, a regional raw material in market expansion is presented as an option for the enrichment of baked foods that do not contain gluten, such as cheese bread.